New and emerging therapies in treatment of Clostridium difficile infection. Issue 6 (June 2018) - Goyal, Hemant; Perisetti, Abhilash; Rehman, M. Rubayat; Singla, Umesh
Abstract : Clostridium difficile infection (CDI) represents one of the most serious nosocomial infections that have grown dramatically over the past decade. Vancomycin and metronidazole are currently used as a standard therapy for CDI. Metronidazole is recommended as a first-line therapy for mild-to-moderate infections and vancomycin is mainly used for severe and/or refractory cases. However, studies have demonstrated that there are quite high CDI relapse rates with both of these medications, which represents a challenge for clinicians. Over the last decade, a number of newer and novel therapeutic options have emerged as promising alternatives to these standard CDI therapies. The following review provides the updated summaries of these newer therapeutic agents and their status in the treatment of CDI.